2019
DOI: 10.3389/fpubh.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences and Hidden Obstacles in Medicine Access in Sub-Saharan Africa

Abstract: Many life-saving drugs are still inaccessible and unaffordable in low- and middle-income countries, particularly in Sub-Saharan Africa. This contributes to poor health outcomes, wider health and socioeconomic inequities, and higher patient spending on healthcare. While resource limitations facing national regulatory authorities (NRAs) contribute to the problem, we believe that (1) fragmented and complex drug regulations, (2) suboptimal enforcement of existing regulations, and (3) poorly designed disincentives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…1.0 1.0 1.1 3.1 A022 0.9 1.1 1.0 3.0 time, more recrudescence, and emergence of resistance. [21][22][23] This becomes very crucial in the treatment of malaria, particularly when artemether is considered for severe malaria cases. As earlier stated, many surveillance studies had reported on the quality of ACTs and other antimalarials in different locations and countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1.0 1.0 1.1 3.1 A022 0.9 1.1 1.0 3.0 time, more recrudescence, and emergence of resistance. [21][22][23] This becomes very crucial in the treatment of malaria, particularly when artemether is considered for severe malaria cases. As earlier stated, many surveillance studies had reported on the quality of ACTs and other antimalarials in different locations and countries.…”
Section: Discussionmentioning
confidence: 99%
“…20 Unfortunately, poor-quality antimalarial drugs are often associated with a high rate of malaria treatment failure and poor health outcomes, as reported in many surveys. [21][22][23][24] Of additional interest is the scourge of development of antimalarial resistance, which has been correlated with the use of substandard antimalarial medicine. 20,22,23 In a survey by Hajjou et al, 25 antimalarial drugs were found to represent 52.5% of all substandard medicines and 92.6% of all falsified drugs detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AU Model Law and AMRH initiative efforts are intended to support countries to rectify some of the regulatory challenges that they have been grappling with for many years [ 15 ]. The long term goal of the AMRH initiative is to establish the African Medicines Agency, which will have the mandate of overseeing the registration of specific medical products and coordinating regional harmonisation systems in Africa [ 14 , 37 ]. Therefore, the AU Model Law’s development is interpreted within the context of these overarching efforts towards regulatory harmonisation in Africa [ 14 ].…”
Section: Country-level Adoption Of the Au Model Lawmentioning
confidence: 99%
“… 103 However, there still exists a deficiency in data, visibility, distribution and illegitimate drug control gap that medicines serialisation technology can fill. 104 These data can be leveraged to ascertain the specific location where an illegitimate drug entered the supply chain, allowing for precision and rapid recall. In addition, it can provide data on the incidence of falsified medicines, which is currently lacking and necessary for quantifying the problem, especially in LMICs.…”
Section: Adaptation Of Interventions From Hics To Lmicsmentioning
confidence: 99%